Reactive power compensation in the combined system of sugar refinery electricity - Shesterenko, Volodymyr; Sydorchuk, Iryna (My University, 2013)
Розглянуто шляхи підвищення ефективності компенсації реактивної потужності на харчових підприємствах. Показано, що застосування конденсаторів індивідуальної компенсації дозволяє відмовитися від складних і дорогих пристроїв регулювання потужності конденсаторних установок, якими необхідно комплектувати установки централізованої компенсації на трансформаторних підстанціях, а захист двигуна від режиму самозбудження можна здійснити шляхом підключення конденсаторів до затискачів двигуна через автоматичний вимикач, обладнаний електромагнітом дистанційного відключення.We consider the ways of increasing operation efficiency of reactive power compensation on the plants. The basic aspects of standardized methods of power compensating devices choice, depending on the voltage and configuration of its individual elements are noticed. The expediency of each synchronous engine usage for reactive power compensation is shown. If the load factor of a synchronous engine is less than 1 (one), it is reasonable to use fully expected reactive power output. It is proved the necessity to apply the power higher harmonics filters with the distortion factor of more than 8%, which is typical for plants with thyristor converters. They are calculated from the computed value of the distortion factor which is based on the composition and level of harmonics. The calculation of filters should be started from the smallest harmonic filter. It is necessary to check the admissibility of filters loading with the current of proper harmonics. The total reactive power generating filters should be chosen from the condition of reactive power balance.
Keywords: реактивна потужність; компенсація, індукції двигуна; системи живлення; реактивная мощность; компенсация; индукция двигателя; система питания; reactive power; compensation; induction engine; supply system; кафедра електропостачання і енергоменеджменту